Nonzygotic Embryogenesis in Passiflora maliformis - Bernal Moreno, Sandra Carolina (2018)
The economic, ecological and medical significance of passion fruits has encouraged the development of multidisciplinary research in this group. In vitro culture, non-zygotic embryogenesis represents an alternative for plant regeneration; however, this technique has presented difficulties in the reproducibility of protocols as well as the development of certain embryos and abnormal plantlets in some species. We assessed in Passiflora maliformis L the morphogenic capacity in the mature zygotic embryos (MZE) to develop non-zygotic embryos (NZE), and subsequent plantlets regeneration. We tested an induction stage with 12 treatments in MS + VitB5 medium supplemented with 2,4-D, KIN and BA added alone or combined and, another with a MS, MS with Activated Charcoal (AC) or MS with growth regulators (GR) in 1/10 concentrations reduced to 1/10 of those added in the induction stage. We obtained high percentages, 70%, of regenerants in the medium supplemented with 1 mgL-1 BA and transferred to the MS expression medium, as well as in the medium with 1 mgL-1 BA + 3 mgL-1 2,4-D, and transferred to the expression medium with AC, 60%. 70% of the regenerated seedlings were successfully grown in the greenhouse. This is the first research that addresses the expression of the MZE embryogenic potential in P. maliformis, inducing a successfully embryogenic non-zygotic responses through direct and indirect routes; the obtained results are relevant to the knowledge of non-zygotic embryogenesis in other passion fruits, for breeding and commercial uses.